Exploration of Health Status, Illness Perceptions, Coping Strategies, Psychological Morbidity, and Quality of Life in Individuals With Fecal Ostomies. Issue 1 (January 2017) - Knowles, Simon R.; Tribbick, Davina; Connell, William R.; Castle, David; Salzberg, Michael; Kamm, Michael A.
Abstract : PURPOSE: In a previous paper focusing on the common sense model (CSM) for ostomies in people with inflammatory bowel disease, cancer, and diverticular disease, we reported that (1) illness perceptions were directly related to illness status, and both illness perceptions and coping strategies (maladaptive coping) directly influenced anxiety and depression; (2) self-efficacy and emotion-focused coping style ameliorated depression but not anxiety; and (3) time since surgery was associated with improved health status, a reduction in negative illness perceptions, and increased emotional-focused coping. The purpose of this article was to perform a secondary analysis with the addition of a stoma quality-of-life measure. SUBJECTS AND SETTING: One hundred fifty adults with ostomies (54 males, and 96 females; mean age = 44 years) completed an online survey. DESIGN: Descriptive, cross-sectional, questionnaire-based study. METHODS: Participants completed the Health Perceptions Questionnaire, Brief Illness Perceptions Questionnaire, Carver Brief Coping Questionnaire, Stoma Self-efficacy Scale, Hospital Anxiety and Depression Scale, and the Stoma Quality-of-Life Scale. RESULTS: Using structural equation modeling, the final model provided an excellent fit to the data (χ 2 27 = 19.20, P = .37, χ 2 /N = 1.08, Standardized Root Mean Square Residual (SRMR) <0.03, Steiger-Lind Root Mean Square Error of Approximation (RMSEA) <0.03, Goodness of Fit Index (GFI) >0.98). Extending upon our previous paper, self-efficacy, anxiety, and depression were found to have a significant direct influence on stoma-specific quality of life (β= .47, P < .001, β=−.25, P < .001, and β=−.35, P < .001, respectively). CONCLUSIONS: The findings of this secondary analysis extends our previous report by identifying that, consistent with the CSM, illness status, illness perceptions, and coping influence health-related quality of life via self-efficacy, anxiety, and depression. The results suggest that to improve an individual's quality of life, psychological interventions should target the psychological processes underpinning mental illness and also help develop and maintain an individual's self-efficacy in relation to ostomy care.